COVID-19 Scenario and Possible Crisis Management Plan in Bangladesh: A Review (Journal of Engineering Science, 2020)
At present novel corona virus (COVID-19) has affected 213 countries around the world. In the context of both developing and less developed countries, it has proven to be fatal. Bangladesh, being a country of low-middleincome economy is still experiencing daily rise of COVID-19 cases. This study investigates the impact of COVID-19 on some important sectors of the country, where the education system is in danger as well as the lion’s share of the inhabitant cascade with poverty. The outcome of the research also states the overall management system has not worked smoothly in the pandemic situation. It focused on the existing emergency crisis response management plan, policy framework and parliamentary organizations of Bangladesh which are not good enough to battle a pandemic such as COVID-19. The secondary data were collected from different credential sources. This research mainly focused on the in-depth analysis of crisis during this time and highlighted the crisis sector management of Bangladesh. Hence, it formulated a proposal on 10 sector-based (education, economic, general public, victim, Government, private sector, defense, medical services, media, social value perception) Crisis Response Management Technique and a committee that would work in post COVID-19 time in Bangladesh. In future, this research and its policy frame work would help the government to allocate the budget for different sectors not only for pandemic situation but also for another crisis and help minimize its catastrophe.Journal of Engineering Science 11(2), 2020, 45-60